Layanan Hotline Konsultasi Masalah Kesehatan Pasca COVID-19 - Sabrina Ermayanti; Russilawati Russilawati; Fenty Anggraini; Afriani Afriani; Irvan Madison; Oea Khairsyaf; Masrul Basyar; Deddy Herman; Yessy Susanty Sabri; Dewi Wahyu Fitrina; Dessy Mirzati; Elsa Purnama Sari; Dimas Bayu Firdaus (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Pandemy of Corona virus disease 2019 (Covid-19) has overwhelmed the word for nearly two years. Indonesia is one countries that been hit hard by Covid-19. Even though most of patients with positive test of Covid-19 had no symptoms or mild some of them reported persistent clinical symptoms months after test negative. This population with disorder whose terminology Long Covid-19 need health care to help them cope with this condition. In this need Department of Pulmonology and Respiratory medicine initiate community service activity for Covid-19 survival with Long Covid-19 in the formulation Hotline Service on Post Covid-19 Health Problem. Survivors of Covid-19 who accessed this service originated from variety geographic region in Indonesia. This Activity reached 60 survivors were mostly female (57%), in age group of young adult (62%) and dominant with mild symptoms (58%). Recommendation for these survivors whose mild symptoms was self care observation. There were still about 25 survivors (42%) who need further health care with appropriate speciality.